Corporate board diversity and state owned enterprises performance in Zimbabwe’s (2011-2015) - Chirume, Takawira (Midlands State University, 2020)
This paper examines the associations between diversity of board members and financial performance of State Owned Enterprises in Zimbabwe (SOEs). Three demographic characteristics of board members, gender, cultural/nationality, and age were used as the proxies for diversity. The study used a positivism philosophy was used and being anchored on the quantitative research design. A survey of 54 SOEs were sampled to include 114directors in the SOEs sector. This study found out that both accounting and market performance have significant negative associations with gender diversity. Nationality diversity is found to have no influence on firm performance. In contrast, the proportion of young members is positively related to market performance, providing evidence that young people in the boardrooms are associated with improved financial performance.